2020
DOI: 10.14202/vetworld.2020.1544-1548
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasite infections in fighting bulls in South Thailand

Abstract: Background and Aim: Bullfighting is booming in South Thailand, attracting tourists, and stimulating local economies. The bulls are well raised and practiced, but in many cases, the owners lack knowledge and understanding of the prevention of animal diseases, including parasitic infections. This study aimed to determine the occurrence of gastrointestinal (GI) parasite infection in fighting bulls. Materials and Methods: A total of 1501 fecal samples were collected from bulls aged 2-5 years visiting the animal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
9
3
Order By: Relevance
“…However, this study found a low prevalence of Fasciola spp. infections, fasciolosis has been identified by the WHO as a remerging neglected tropical disease associated with endemic and epidemic outbreaks of diseases in human populations [19]. Our findings indicate that the high prevalence of Fasciola spp in Kalasin Province may relate to the location of Kalasin Province which is adjacent to Lampao dam, resulting in the appropriate temperature and humidity for promoting the intermediate host population growth such as intermediate snail hosts and water vegetables [31,32].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, this study found a low prevalence of Fasciola spp. infections, fasciolosis has been identified by the WHO as a remerging neglected tropical disease associated with endemic and epidemic outbreaks of diseases in human populations [19]. Our findings indicate that the high prevalence of Fasciola spp in Kalasin Province may relate to the location of Kalasin Province which is adjacent to Lampao dam, resulting in the appropriate temperature and humidity for promoting the intermediate host population growth such as intermediate snail hosts and water vegetables [31,32].…”
Section: Discussionmentioning
confidence: 72%
“…In bulls, the main infection was caused by Paramphistomum spp. (97.17%), but strongyles infection was low (26.29%) [19]. Fasciola spp.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The distribution of rumen fluke infecting ruminants has been well documented globally owing to the economic importance from the veterinary standpoint (Huson et al, 2017;Nisar et al, 2021;Pfukenyi & Mukaratirwa, 2018), with a broad geographical spread, particularly in Nigeria, Thailand, and India (Dube, 2010;Kaewnoi et al, 2020;Malathi et al, 2021). Different rumen fluke species predominated in other parts of the world (Rafiq et al, 2020).…”
Section: Epidemiological Factors Of Rumen Fluke In Cattle and Buffaloesmentioning
confidence: 99%
“…The common species of snails that can act as intermediate hosts of rumen fluke reported from different Asian countries include Radix rubiginosa, Radix auricularia, Lymnaea truncatula, Lymnaea stagnalis, Lymnaea natalensis, Lymnaea palustris, Lymnaea viridis, Lymnaea luteola, Bulinus truncates, Bulinus furskalii, and Indoplanorbis exustus (Dodangeh et al, 2019;Dung et al, 2013;Martin & Cabrera, 2018;Mohammed et al, 2016). Therefore, rumen fluke is found at high prevalence in most tropical and sub-tropical countries such as Bangladesh, Thailand, Indonesia, and India (Azam et al, 2012;Kaewnoi et al, 2020;Hambal et al, 2020;Malathi et al, 2021), particularly in locations where the climatic and environmental conditions are favourable for the intermediate host snail's survival and multiplications (Gordon et al, 2013;Taylor et al, 2007). Also, these intermediate hosts play an essential role in completing the life cycle of rumen fluke and transmitting the disease (Lotfy et al, 2010;Pfukenyi & Mukaratirwa, 2018).…”
Section: Snail Intermediate Hostmentioning
confidence: 99%